Three new species and new faunistic data on Ancistria Erichson (Coleoptera: Passandridae) from southern China - Pan, Zhao; Li, Pan-Pan; Liu, Kai-Xuan; Shu, Zu-Fei; Zhang, Ying-Ming; Bai, Ming (Zootaxa, 2024)
Ancistria Erichson, 1845 is poorly known from China, with only five species recorded. Three new species and one newly recorded species for China were discovered from the Nanling Mountain Range and Lingnan area, i.e., A. limbata Pan, sp. nov., A. longior Pan, sp. nov., A. nanlingensis Pan, sp. nov. and A. bicolorata Burckhardt & Ślipiński, 1995, which are described and illustrated in this paper. A key to the known Chinese species of Ancistria is also provided.